Efektivitas Pijat Kaki pada Lansia dengan Nyeri Sendi di UPTD Pelayanan Sosial Lanjut Usia Binjai Tahun 2024 - Petra Diansari Zega; Ali Imran Sirait; Yurnita Batee; Abdul Hafizh Al Rasyid Siregar (Lembaga Pengembangan Kinerja Dosen, 2025)
Rheumatoid Arthritis is an autoimmune disease.. This system attacks joints and other parts of the body such as tendons, ligaments, and bones. One implementation of reducing rheumatoid arthritis pain is to massage the feet of the painful joints. This study used a quasi-experimental design. The population in this study was 48 people and the research sample was 20 people with two groups, namely the experimental group and the control group. The results of the study were obtained after rheumatoid arthritis foot massage had a significant effect in reducing pain in the experimental group with a p-value of 0.007. Foot massage on painful joints has benefits in reducing the pain scale in the elderly.